Malay (and Javanese) loanwords in Frederick de Houtman’s Malagasy wordlist - Adelaar, Alexander (Wacana, Journal of the Humanities of Indonesia, 2024)
Frederick de Houtman’s Malagasy language material (1603) consists of a wordlist and short prose texts. It represents a dialect spoken more than four hundred years ago in the Antongil Bay region on Madagascar’s northeast coast, which does not have a documented modern descendant. This chapter investigates Malay and (to a lesser extent) Javanese loanwords found in this material. Most of these loanwords are demonstrably old and can be dated to an era preceding the Malagasy migrations to eastern Africa thirteen centuries ago. They provide invaluable insights into the world of the early migrants to Madagascar and the degree of their exposure to major civilizations in insular Southeast Asia before their departure from Borneo. Another important aspect of these loanwords is that they hold unique information about Malay and Javanese lexical history. Finally, that Houtman’s material represents Madagascar’s oldest historiolect only adds to the appeal of these data.